Effective Classroom Management: Proven Techniques to Fostr Engagement and Minimize Discruptions - Iskandar, Edi; Irawati, Irawati; Chai, Nong (Journal of Educational Teaching and Trends, 2025)
Maintaining classroom discipline poses significant challenges in today’s educational landscape, as UNESCO data indicates a global loss of 25% of teaching time due to disruptions. Growing student diversity and post-pandemic behavioral concerns have intensified these issues, necessitating research-backed approaches that foster engagement while minimizing distractions. Although various management strategies exist, their efficacy differs substantially depending on cultural and developmental contexts, often leaving educators uncertain about best practices.  This research assesses universally effective classroom management methods, analyzing their influence on student participation, academic performance, and behavioral incidents. Utilizing a mixed-methods design, the study examined 120 peer-reviewed articles (2015–2023) from Scopus and ERIC, alongside observational data from 15 countries. Findings revealed that proactive measures-such as structured routines and positive reinforcement-curbed disruptions by 40-65%, surpassing reactive interventions. The most successful strategies emphasized consistency, student independence, and cultural relevance. Notably, digital tools (e.g., token economies) improved adolescent compliance by 28% compared to traditional systems.  The study concludes that flexible, culturally adaptive frameworks-not rigid protocols-are key to effective management. To enhance learning environments globally, policymakers must invest in teacher training focused on proactive, inclusive techniques.